The Effect of Back and Hand Massage Intervention on Pain in Patients Post-Cardiac Catheterization - Fazarudin Fazarudin; Irna Nursanti; Wati Jumaiyah; Dhea Natashia; Ii ismail (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cardiac catheterization is an invasive procedure that involves the insertion of one or more catheters into the heart and certain blood vessels to visualize the heart chambers, valves, great vessels, and coronary arteries. Prolonged immobilization in patients after cardiac catheterization can cause complications, one of them is back pain. The nursing intervention in this study was back and hand massage. This study aims to determine the effectiveness of back and hand massage interventions on pain in patients after cardiac catheterization. This study used a quasi-experimental method with a pre-test and post-test design, with an intervention group and a control group design. The sampling technique used purposive sampling. The sample size was 36 patients who had cardiac catheterization, calculated using the Federer formula. The intervention group received a total of 20 minutes of massage therapy: 10 minutes of back massage, 10 minutes of hand massage, the first period was carried out after the sheath was removed, and the second period was carried out after the elastic bandage was removed. The data analysis technique used multivariate with the Generalized Linear Model (GLM) Repeated Measures (RM) method. The results showed that back and hand massage had an effect on pain in post-cardiac catheterization patients, with a P value of 0.000. This indicates decreasing a pain scores after the intervention. Multivariate testing indicated that previous experience with catheterization pain influenced pain in post-catheterization patients. Back and hand massage intervention is expected to be an alternative supportive intervention, especially in post-catheterization patients, in reducing pain.